Faktor-Faktor Yang Berhubungan Dengan Kejadian Stunting Pada Balita Di Wilayah Kerja Puskesmas Puuwatu Kota Kendari - La Ode Liaumin Azim (STIKES Columbia Asia Medan, 2025)
Stunting is a significant public health problem in Indonesia, especially among toddlers. Stunting can have long-term effects on children's quality of life, including physical growth and cognitive development disorders. The Puuwatu Community Health Center in Kendari City has recorded a high rate of stunting. Therefore, it is important to identify the factors associated with stunting in this area. This study aims to identify factors associated with stunting in toddlers in the working area of the Puuwatu Health Center in Kendari City. This study uses an analytical study design with a cross-sectional approach. The sample in this study consisted of 73 respondents, and sampling was conducted using stratified random sampling taken from each urban village. Data were collected through interviews with parents of toddlers experiencing stunting, as well as measurements of the toddlers' nutritional status. Data analysis was performed using the chi-square statistical test to examine the relationship between the variables studied. This study shows that nutritional intake (p value = 0.002), exclusive breastfeeding (p value = 0.000), and income (p value = 0.439) are related to stunting. It can be concluded that there is a relationship between nutritional intake and exclusive breastfeeding with the incidence of stunting, while income is not related to the incidence of stunting in the working area of the Puuwatu Community Health Center.